PENINGKATAN KETERAMPILAN MENULIS MENGGUNAKAN PENDEKATAN KOMUNIKATIF BAGI SISWA KELAS X SMK MULTIMEDIA NURUL HUDA PONCOKUSUMO MALANG - Werdiningsih, Endang; Sutrisno, Edy (Jurnal Likhitaprajna, 2019)
Writing for most students is a language skill that is difficult to master. This research on writing skills is based on observations and experiences of researchers towards the low ability of SMK students in writing. This is because learning to write at school is still conventional. The selection of learning models has not been a top priority by teachers. The communicative model can be used to improve writing learning to foster a sense of writing and improve learning outcomes. The results of the act of using a communicative approach to writing activities at SMK Multimedia Nurul Huda Poncokusumo showed an increase when compared to conventional writing learning. Improving the ability of students in writing occurs through several stages carried out in three cycles using the communicative model.Keyword: writing, communicative model, learning